Analysis of residual stresses and durability of the cutting inserts after diamond-spark grinding - Sizyi, Yury; Strelchuk, R. M.; Jha, Shailendra Kumar; Rudnev, Alexander; Gutsalenko, Yury (Editura "Academica Brâncuşi", Târgu Jiu, 2020)
The article presents an analysis of residual stresses and resistance of cutting inserts after the diamond-spark grinding. In the entire investigated range of traverses (0.01...0.07mm/double stroke) and wheel speed (18...32m/s), the total residual oriented stresses in both phases are compressive and they have an extreme character with a point of extremum (minimum) in the center of the interval (Sпоп = 0.04mm/double stroke; Vкр = 25m/s). In the carbide phase, the main share in the formation of the total stress state of the surface layer of the STIM-3B (СТИМ-3Б) hard alloy is made by macrostresses. The mechanism of their formation is thermal at small and large values of the traverse and wheel speed, and power one—at medium values. The importance of interfacial microstresses in this phase is minor. In the binding phase of nickel, the interfacial component contributes significantly to the formation of the general stress state, due to the force factor at average values of the grinding mode mechanical parameters and thermal parameters in the rest of the range. The highest wear resistance of tools made of STIM-3B (СТИМ-3Б) alloy corresponds to the highest value of compressive interfacial microstresses in the plastic phase (Ni).
Keywords: residual stresses; grinding wheel; carbide; tool durability